Autophagy suppresses self-renewal ability and tumorigenicity of glioma-initiating cells and promotes Notch1 degradation. Issue 11 (November 2018) - Tao, Zhennan; Li, Tao; Ma, Haiwen; Yang, Yihan; Zhang, Chen; Hai, Long; Liu, Peidong; Yuan, Feng; Li, Jiabo; Yi, Li; Tong, Luqing; Wang, Yingshuai; et al.
Abstract Autophagy is a vital process that involves degradation of long-lived proteins and dysfunctional organelles and contributes to cellular metabolism. Glioma-initiating cells (GICs) have the ability to self-renew, differentiate into heterogeneous types of tumor cells, and sustain tumorigenicity; thus, GICs lead to tumor recurrence. Accumulating evidence indicates that autophagy can induce stem cell differentiation and increase the lethality of temozolomide against GICs. However, the mechanism underlying the regulation of GIC self-renewal by autophagy remains uncharacterized. In the present study, autophagy induced by AZD8055 and rapamycin treatment suppressed GIC self-renewal in vitro. We found that autophagy inhibited Notch1 pathway activation. Moreover, autophagy activated Notch1 degradation, which is associated with maintenance of the self-renewal ability of GICs. Furthermore, autophagy abolished the tumorigenicity of CD133 + U87-MG neurosphere cells in an intracranial model. These findings suggest that autophagy regulating GICs self-renewal and tumorigenicity is probably bound up with Notch1 degradation. The results of this study could aid in the design of autophagy-based clinical trials for glioma treatments, which may be of great value.